Studies on Ethnoveterinary Uses of Plant Resources of Sikkim - Bharati, Kumar Avinash; Sharma, B. L. (Indian Forester, 2009)
A field study was done to study and document the indigenous knowledge of various ethnic groups of Sikkim regarding animal healthcare. A large number of plants was collected and the information on their ethno-veterinary uses was gathered from local inhabitants. The information about folk medicinal use, vernacular names of plants and the parts of the plants used are documented. During the investigation, a well developed ethno-veterinary system among tribal people was observed. 19 species of plants were recorded, which are used by local people to cure various diseases and disorders. The basic aim of the study was to document knowledge and conserve these medicinal plants.